Study of The Electric Field Between Horizontal and Vertical Configuration Pole under 150 KV High Voltage Transmission Line (SUTT 150 KV) - Amrita, Anak Agung Ngurah (Journal of Electrical, Electronics and Informatics; Vol 1 No 2 (2017): JEEI (September 2017), 2017)
Distribution of electrical energy from a plant to a substation or from a substation to other substations usually uses a transmission line. In Bali, type of transmission line that is usually implemented is SUTT 150 kV. The magnitude of the applied voltage is an attempt to reduce power loss for long distance distribution. However, distributing electrical energy with increasing stress affects the increase of electric field around the transmission line. The negative impact of electricity distribution has been an environmental problem for PT. PLN (Persero), especially where there is conversion from an open area to be a residential. This problem has been the main reason for conducting this research. IRPA / INIRC recommendation states that exposure time is not limited to the electric field effect in work environment and public area including a residential area at frequency of 50/60 Hz is 5 kV/m.  This recommendation is in accordance with SNI 04-6950-2003, on Threshold Limit Values ??Electric Field under SUTT and high-voltage wires. The first problem of this research is how large the intensity of the electric field between two poles of SUTT 150 kV with vertical and horizontal constructions which are built side by side? The second problem is what the characteristic of the electric field intensity between the two poles which are built side by side? From the analysis, it can be seen that the intensity of the electric field that occurs between the conductor of the vertical and horizontal pole configurations are still below the IRPA/INIRC and SNI 04-6950-2003 recommendation i.e. 1 up to 1.5 kV/m and at a distance of 18 meters to 25 meters there is an interaction of electric field intensity that occurs at these two configurations.